Folic acid, vitamin B12 and homocysteine levels following olanzapine administration in schizophrenia patients - Hasnat, Fahmida; Dewan, Zesmin F.; Misbahuddin, Mir; Akhter, Nargis; Shamsunnahar, Jhunu; Bhuiyan, Habiba Akhter (Bangabandhu Sheikh Mujib Medical University Journal, 2018)
The purpose of this study was to assess the levels of folic acid, vitamin B12 and homocysteine in the serum of schizophrenia patients (n=20) and to evaluate the effect of olanzapine on these biomarkers. The blood was also collected from the 10 healthy volunteers as control. Compared to control, the serum folic acid (p=0.005) and vitamin B12 levels (p=0.211) were higher in the schizophrenia patients, whereas no difference was evident in the serum homocysteine level. But significantly higher levels of serum folic acid (p=0.005), vitamin B12 (p=0.047) and significantly lower level of serum homocysteine (p=0.000) were observed after 10 weeks of olanzapine administration. BPRS score was reduced significantly after intervention. The Pearson correlation coefficient test showed a statistically not significant negative relationship between the serum folate, vitamin B12 and homocysteine levels. In conclusion, olanzapine can significantly elevate the serum folic acid and vitamin B12 levels whereas it can lower the serum homocysteine level which may contribute to the improvement of symptoms of schizophrenia.